Ethnography of Horse Racing Gamblers’ Lives. Constructing Biographical Narratives in the Process of Interviewing - Bossak-Herbst, Barbara; Głowacka-Grajper, Małgorzata (Qualitative Sociology Review, 2023)
In this paper, we analyze the narrative strategies employed by horse racing gamblers in the context of their interactions within interviews. The empirical base consisted of 20 semi-structured interviews conducted with long-term regular gamblers from Warsaw, Poland. First, we state our position in the context of interviews with people aware they may be assessed negatively regarding a very important part of their lives. Second, we discuss how the interlocutors presented their biographies and employed discursive methods of protection against negative interpretation. The research reveals how bettors justify their passion by referring to individual myths about the origins of their interest in gambling. We reveal how bettors consciously employ emotive discursive methods that alleviate the discourse of addiction. Emotions are not presented as triggered by compulsively realized needs but as a result of intellectual passion, pursued by like-minded people joined by a drive for agency.